Levels of Integration in Children's Early Clause Combining in Hebrew. Issue 3 (3rd July 2021) - Lustigman, Lyle; Berman, Ruth A.
ABSTRACT: The study examines phases in developing specification of grammatical marking of emergent clause-combining (CC) as indicative of children's growing ability to integrate two or more independent predications. To this end, both intra- and inter-clausal analyses were applied to all CC utterances produced by three Hebrew-acquiring children aged 2;0–3;0, covering both child autonomous productions and adult-child co-constructed CC. Based on four phases in CC construction shared by the three children, the following developmental trends were identified for both coordination and subordination in our database. First, children start combining two predications with lexical verbs early on, but these are confined to non-marked or adult-supported constructions. Second, early connective-marked CC involves mainly verbless copular or existential clauses. And autonomously produced lexical-verb combinations marked by connectives emerge several months later. This initial "trade-off" and gradual progression in grammatical specificity to full-fledged, lexically marked CC is interpreted as reflecting the developmental route of children's early clause integration in interactive discourse.